METAL RESEARCH OF THE REASONS OF BREAKAGE AT DRAWING OF ROLLED WIRE OF STEEL SV-08G2S - A. M. Nesterenko; A. B. Sychkov; S. Ju. Zhukova (Литьë и металлургия)
Metallurgical reasons of metal breakage at wire drawing, connected with microstructure of rolled wire, are examined.